The clinical, functional, and radiological features of hand osteoarthritis: TLAR-osteoarthritis multi-center cohort study - Selda Sarıkaya,; Ece Kaptanoğlu,; Taciser Kaya,; Hilal Ecesoy,; Meltem Alkan Melikoğlu,; Kemal Nas,; Hakan Nur,; Şüheda Özçakır,; Merih Sarıdoğan,; Cahit Kaçar,; İlhan Sezer,; Dilşad Sindel,; et al. (Archives of Rheumatology, 2022)
Objectives: This study aims to evaluate the clinical, functional, and radiological features of hand osteoarthritis (OA) and to examine their relationships in different geographic samples of the Turkish population. Patients and methods: Between April 2017 and January 2019, a total of 520 patients (49 males, 471 females; mean age: 63.6±9.8 years) with hand OA were included in the study from 26 centers across Turkey by the Turkish League Against Rheumatism (TLAR). The demographic characteristics, grip strengths with Jamar dynamometer, duration of hand pain (month), the severity of hand pain (Visual Analog Scale [VAS]), and morning stiffness were evaluated. The functional disability was evaluated with Duruöz Hand Index (DHI). The Kellgren-Lawrence (KL) OA scoring system was used to assess the radiological stage of hand OA. Results: The DHI had significant correlations with VAS-pain (r=0.367, p<0.001), duration of pain (r=0.143, p=0.001) and bilateral handgrip strengths (r=-0.228, p=0.001; r=-0.303, p<0.001). Although DHI scores were similar between the groups in terms of the presence of hand deformity (p=0.125) or Heberden's nodes (p=0.640), the mean DHI scores were significantly higher in patients with Bouchard's nodes (p=0.015). The total number of nodes had no significant correlations with the VAS-pain and DHI score (p>0.05). The differences between the groups of radiological hand OA grades in terms of age (p=0.007), VAS-pain (p<0.001), duration of pain (p<0.001), and DHI (p<0.001) were significant. There were no significant differences between radiological hand OA grades according to the duration of the stiffness, grip strength, and BMI (p>0.05 for all). Conclusion: In our population, the patients with hand OA had pain, functional disability, and weak grip strength. The functional impairment was significantly correlated with the severity of the pain, and the functional status was worse in high radiological hand OA grades.